Faktor Penyebab dan Upaya Mengatasi Prokrastinasi Akademik Peserta Didik Pada Masa Pandemi Covid-19 - Mischel Ruth Berkati Zega (Bulletin of Counseling and Psychotherapy, 2022)
This study focuses on the behavior of students' academic procrastination during the COVID-19 pandemic. This study aims to determine the causal factors and efforts to overcome the academic procrastination of students at SMP Negeri 6 Salatiga during the covid-19 pandemic. This study uses a qualitative descriptive approach and type of research. In this study, researchers used purposive sampling (non-probability) to determine informants based on criteria. The location of this research is SMP Negeri 6 Salatiga. The research subjects consisted of one BK teacher and four students with predetermined criteria. Data collection methods used in this study were interviews and documentation. Test the validity of the data using triangulation techniques. The data analysis technique in this study uses the Miles and Huberman model. The results of this study found that 1) the factors causing students' academic procrastination during the pandemic were caused by two factors, namely internal factors and external factors. Internal factors consist of health conditions, motivation, self-efficacy, self-control, and self-awareness. Meanwhile, external factors consist of parenting patterns and environmental conditions. 2) BK teachers' efforts to overcome academic procrastination by conducting home visits, information services and consultations. Then, coordinate with homeroom teachers and subject teachers.